Effect of S-curve laser power for power distribution control on laser oscillating welding of 5A06 aluminum alloy. (May 2022) - Tan, Zhejun; Pang, Bowen; Oliveira, J.P.; Chen, Long; Bu, Xianzheng; Wang, Zhimin; Cong, Baoqiang; Zeng, Zhi
Highlights: A S-curve power of laser oscillating welding is proposed. The grains in the welded joint with S-curve power were refined, and the mechanism of grain refinement is analyzed. Compared with joints with constant power, the tensile strength with S-curve laser power was increased by 35.3% and could reach 99.1% of the base metal strenght. Abstract: Laser oscillating welding of 5A06 aluminum alloy is widely used in industry. In order to improve the performance of Al-based welded joints and reduce welding defects, this paper details the effects of employing an S-curve laser power which is distributed along the laser oscillating path (sine wave) to improve the microstructure and mechanical properties of the joints. By applying the S-curve and an equal power condition to the 5A06 aluminum alloy, bottom butt sinusoidal path laser oscillating welding was performed. The welding appearance, microstructure and mechanical properties of the welded joints under two laser oscillating welding processes were investigated. Our results showed that laser oscillating welding using the S-curve power allows to obtain good joints when compared to the joints produced with constant power. When the linearly varying laser power of "high-low-high" applied periodically was employed, the grains in the joint structure showed the cyclic "growth-inhibition-growth" phenomenon. This growth mechanism not only refined the grain structure, but also narrowed the columnar region, and improved the mechanical properties of the joint. Compared with the laser oscillating process with constant power, the tensile strength of the joints using the S-curve power was increased by 35.3 %. Moreover, the tensile strength of the welded test coupons with S-curve power was 337 MPa, which is about 99.1% of the base metal (340 MPa). The welded joints using the S-curve power showed larger and deeper dimples, highlighting higher ductility and good plasticity. This paper provides a new approach for the research of laser oscillating welding and the control of laser power to improve the mechanical properties of welded joints.